EFFICIENCY OF QUADS ALGORITHM IN COMPLEMENTARY SEQUENCE SEARCH - Abdul Aziz, Maulana
The biggest obstacle in complementary sequence search is the high time complexity, especially when the search method used has an exponential complexity. The complementary sequence search is important because it is used in the construction of Hadamard matrices, which have many applications in technology. To improve computational efficiency, algorithm optimization is required, one of which is to use the Quads algorithm. The Quads algorithm utilizes the combinatoric properties of the complementary sequence to constrain and minimize the search space. The results show that the Quads algorithm is very effective in improving the search efficiency, especially at higher order. The Quads algorithm is also shown to be more effective than brute force search with parallelization. This confirms the importance of algorithm optimization in addressing computationally intensive challenges.